Detection of antisense protein (ASP) RNA transcripts in individuals infected with human immunodeficiency virus type 1 (HIV-1). (21st March 2019) - Mancarella, Antonio; Procopio, Francesco A.; Achsel, Tilmann; De Crignis, Elisa; Foley, Brian T.; Corradin, Giampietro; Bagni, Claudia; Pantaleo, Giuseppe; Graziosi, Cecilia
Abstract : The detection of antisense RNA is hampered by reverse transcription (RT) non-specific priming, due to the ability of RNA secondary structures to prime RT in the absence of specific primers. The detection of antisense RNA by conventional RT-PCR does not allow assessment of the polarity of the initial RNA template, causing the amplification of non-specific cDNAs. In this study we have developed a modified protocol for the detection of human immunodeficiency virus type 1 (HIV-1) antisense protein (ASP) RNA. Using this approach, we have identified ASP transcripts in CD4+ T cells isolated from five HIV-infected individuals, either untreated or under suppressive therapy. We show that ASP RNA can be detected in stimulated CD4+ T cells from both groups of patients, but not in unstimulated cells. We also show that in untreated patients, the patterns of expression of ASP and env are very similar, with the levels of ASP RNA being markedly lower than those of env . Treatment of cells from one viraemic patient with α-amanitin greatly reduces the rate of ASP RNA synthesis, suggesting that it is associated with RNA polymerase II, the central enzyme in the transcription of protein-coding genes. Our data represent the first nucleotide sequences obtained in patients for ASP, demonstrating that its transcription indeed occurs in those HIV-1 lineages in which the ASP open reading frame is present.